Executive functions, parental punishment, and aggression: Direct and moderated relations. (2nd November 2017) - Fatima, Shameem; Sharif, Imran
ABSTRACT: The main focus of the current study was to assess whether executive functions (EFs) moderate the effect of parental punishment on adolescent aggression. The sample were 370 participants (53% girls, 47% boys) enrolled at secondary and higher secondary levels and ranged in age between 13–19 years (M = 15.5, SD = 1.3). Participants were assessed on a self-report measure of aggression and two punishment measures, in addition to a demographic sheet. Then, they were individually assessed on four tests taken from the Delis–Kaplan Executive Functions System (D-KEFS) namely Trial Making Test (TMT), Design Fluency Test (DFT), Color Word Interference Test (CWIT), and Card Sorting Test (CST) to assess cognitive flexibility, nonverbal fluency, inhibition, and problem-solving ability, respectively. Correlation coefficients indicated that all four executive functioning measures and the two punishment measures were significantly correlated with aggression. Moderation analysis indicated that all EFs moderated the relationship between physical punishment and aggression, and only inhibition and problem-solving ability, but not cognitive flexibility and nonverbal fluency, moderated the relations between symbolic punishment and aggression. The findings support the hypothesis that EFs are protective personal factors that promote healthy adolescent adjustment in the presence of challenging environmental factors.